Luv ya bunches : a flower power book - Myracle, Lauren, 1969- (New York : Amulet Books, 2010)
Four friends--each named after a flower--navigate the ups and downs of fifth grade, in a story told through text messages, blog posts, screenplay, and straight narrative.
Reprint. Originally published: 2009.
710
Accelerated Reader AR
Keywords: Friendship -- Juvenile fiction; Schools -- Juvenile fiction